PRODUKTIVITAS DAN PENDAPATAN KERAJINAN TAS DAN KERANJANG ROTAN (Calamus spp) PADA KELOMPOK LESTARI DI KOTA BUNTOK KABUPATEN BARITO SELATAN KALIMANTAN TENGAH - Liya Regita; Sunardi Sunardi; Wiwin Tyas Istikowati (Universitas Lambung Mangkurat, 2020)
One of the non-timber forest products known to the community is rattan. Rattan (Calamus spp) is used as a raw material for the handicraft industry, Kelompok Lestari is a small industry that has the skills in making rattan crafts in order to improve the family economy and play a role in utilizing human resources by utilizing business time in the field of rattan crafts. The development of the craft industry is aimed at expanding employment opportunities and utilizing natural resources and human resources and of course influenced by factors of productivity and income from crafting rattan produced. This study aims to analyze the amount of productivity and income in the rattan handicraft industry (Calamus spp) in the Kelompok Lestari in Buntok City, South Barito Regency, Central Kalimantan. This study uses the observation method in the center of rattan crafts and interview methods, namely interview activities using a questionnaire. The results obtained from this study are the average productivity of craftsmen of rattan bags woven products of 5.1 pieces/month and woven rattan baskets of 5.1 pieces/month. The average income of rattan woven craftsmen in one month is based on the type of rattan bag woven products of Rp.375,714.- and woven rattan basket is Rp.745,114.Keywords: Rattan (Calamus spp); Productivity; Income